(3JMQjQ cJGH CUhd GdgfOSI hGdMSGH dChbdjOSs - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , (B672 (3g` s; (3GbdjOSs
(3ChdgG (B:s
,(3HYO adeG aQZJ ef JMQjQ GdeLSWi QCjJ Gf CMQQ cJGH CUhd GdgfOSI hGdMSGH GdefShH Edi EbdjOS s
(3BNQgG (B:s
(3aEf RhGjG cd hGMOI efgG HYOI bhGYO Je GdcJGH s
(3GdfSNI HgG MhGTs
(3fSNI QGHYIs
(3JHUQI GdYfhGf (B:s
(3JQLeI(B/(3fbds
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdQjGVjGJs